Steam exploded pine wood burning properties with particle size dependence. (15th April 2017) - Saeed, Muhammad Azam; Anez, Nieves Fernandez; Andrews, Gordon E.; Phylaktou, Herodotos N.; Gibbs, Bernard M.
Abstract: Power generation using waste material from the processing of agricultural crops can be a viable biomass energy source. However, there is scant data on their burning properties and this work presents measurements of the minimum explosion concentration (MEC), flame speed, deflagration index (Kst ), and peak pressure for pulverised pine wood and steam exploded pine wood (SEPW). The ISO 1 m 3 dust explosion vessel was used, modified to operate on relatively coarse particles, using a hemispherical dust disperser on the floor of the vessel and an external blast of 20 bar compressed air. The pulverized material was sieved into the size fractions <500 μm, <63 μm, 63–150 μm, 150–300 μm, 300–500 μm to study the coarse particles used in biomass power generation. The MEC (Ø) was measured to be leaner for finer size fraction with greater sensitivity of explosion. The measured peak Kst was 43–122 bar m/s and the maximum turbulent flame speeds ∼1.4–5.4 m/s depending on the size distribution of the fraction. These results show that the steam exploded pine biomass was more reactive than the raw pine, due to the finer particle size for the steam exploded biomass.